Role of Ficus deltoidea extract in the enhancement of wound healing in experimental rats - Abdulla, M.A.; Ahmed, K.Abdul-Aziz; Abu-Luhoom, F.M.; Muhanid, M. (Scientific Publishers India, 2010)
The aqueous extract of Ficus deltoidea whole plant was investigated to evaluate the rate of wound healing enclosure and the histology of healed wounds in rats. Five groups of adult male Sprague Dawley rats were experimentally wounded in the posterior neck area. Group 1 animals were treated with sterile deionized water as a negative control. Thin layer of blank placebo was applied topically to the wounds of Group 2 rats. Group 3 and 4 rats were dressed topically with thin layer of placebo containing 5% and 10% F. deltoidea extracts, respectively. Thin layer of Intrasite gel was applied topically to wounds of Group 5 as a positive control. Grossly, wounds treated with placebo containing 5%, 10% F. deltoidea extract or Intrasite gel significantly accelerated the rate of wound healing compared to wounds treated with sterile deionized water or dressed with blank placebo. Histological analyses of healed wounds were consistent with the results of gross evaluations. Healed wounds dressed with placebo containing 5%, 10% F. deltoidea extracts or Intrasite gel showed significantly lesser scar width at the wound enclosure and more fibroblast proliferation, collagen fibers accompanied with angiogenesis in the granulation tissue than blank placebo-treated wounds. Additionally, no macrophages were seen in the extract-treated wounds compared to the wounds dressed with sterile demonized water or blank placebo. These results strongly document the beneficial and significant effects of F. deltoidea extract to accelerate the rate of wound healing enclosure in the experimentally-induced wounds in rats.